Dilated thoracoabdominal and epigastric veins in a hemodialysis patient with SVC occlusion: case report and literature review - Zhou, Yanlin; Tu, Bo; Wan, Ziming (Frontiers in Cardiovascular Medicine, 2025)
IntroductionFor several reasons, the incidence of superior vena cava(SVC) obstruction continues to rise, as a serious complication of hemodialysis(HD) access, and is becoming a major cause of access depletion. It is also the most difficult challenge for vascular access workers. Here we present the case of a HD patient with complete SVC occlusion, and why no intervention was made.Case presentationA 50-year-old man on maintenance HD was admitted for markedly dilated thoracoabdominal wall veins and superficial epigastric veins. Digital subtraction angiography(DSA) revealed a complete occlusion of the SVC. Treatment options include interventional therapy, closing the arteriovenous fistula(AVF) to reduce venous pressure and creating a new lower extremity arteriovenous(AV) access, or open surgery. The patient's venous hypertension syndrome and AV access function were carefully evaluated, leading to a decision for conservative management without immediate intervention. After five years of follow-up, his left forearm AVF continues to function well, and both the AVF and superficial epigastric veins can be used for HD access.ConclusionThe management of central venous stenosis(CVS)/obstruction continues to present significant challenges. Presently, endovascular treatment is associated with low primary patency rates and a high risk of complications. Patient-centered decision-making plays a crucial role in the management of CVS/obstruction.This study provides significant insights into the conservative management in complete SVC occlusion, characterized by comparable excellent collateral compensation.